An unusual manifestation of diabetic ketoacidosis and acute colonic pseudo-obstruction. (May 2017) - Natalini, Jake; Borno, Hala; Jin, Lan; Jensen, Trevor
Lesson: Patients presenting with diabetic ketoacidosis and acute colonic pseudo-obstruction should undergo a focused evaluation to identify underlying precipitants.